NON-LINEAR PROFESSIONS IN EDUCATIONAL INSTITUTIONS: AN ANALYSIS OF LEADERSHIP STYLE PERSPECTIVES AND PRINCIPALS' RESPONSES IN LOMBOK - Syaharuddin, Syaharuddin; Fitriani, Mohamad Iwan; Mashwani, Hazrat Usman (Universitas Muhammadiyah Mataram, 2025)
Abstract: The modern technology-based era has led to the emergence of non-linear professions in education, especially principals and teachers. Therefore, the purpose of this study is to analyze in depth about the evolution of non-linear professions that affect the role of leadership in educational institutions, as well as knowing the principal's response to non-linear professions in educational institutions. This research uses qualitative with a library research approach and descriptive qualitative. The data taken at the library research stage is limited to articles published in the last 10 years. Furthermore, we distributed questionnaires to school principals to find out the responses, obstacles, and solutions they apply to non-linear professions in their respective institutions. The results showed that effective leadership to overcome non-linear professions are transformational leadership, adaptive leadership, visionary leadership, and liquid leadership. The response results of 61 principals stated that 80% of principals stated that the existence of non-linear teachers contributed positively to the achievement of educational goals and 77.74% of non-linear teachers needed moral support and more intensive supervision. Furthermore, the limitations of non-linear teachers' professionalism can be overcome by improving hard and soft skills through study group activities, short courses, and regular supervision and evaluation.